Tissue repair and the dynamics of the extracellular matrix. - Midwood, K; Williams, L; Schwarzbauer, J (2004)
Repair of tissue after injury depends on the synthesis of a fibrous extracellular matrix to replace lost or damaged tissue. Newly deposited extracellular matrix is then re-modeled over time to emulate normal tissue. The extracellular matrix directs repair by regulating the behavior of the wide variety of cell types that are mobilized to the damaged area in order to rebuild the tissue. Acute inflammation, re-epithelialization, and contraction all depend on cell-extracellular matrix interactions and contribute to minimize infection and promote rapid wound closure. Matricellular proteins are up-regulated during wound healing where they modulate interactions between cells and the extracellular matrix to exert control over events that are essential for efficient tissue repair. Here, we discuss how the extracellular matrix changes during the stages of tissue repair, how matricellular proteins affect cell-extracellular matrix interactions, and how these proteins might be exploited for use therapeutically.